2021
DOI: 10.3390/ma14185358
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Strain Capacity by the Introduction of Pearlite in Bainite and Polygonal Ferrite Dual-Phase Pipeline Steel

Abstract: In this study the strain capacity and work-hardening behavior of bainite (B), bainite + polygonal ferrite (B + PF), and bainite + polygonal ferrite + pearlite (B + PF + P) microstructures are compared. The work hardening exponent (n), instantaneous work hardening value (ni), and differential Crussard-Jaoul (DC-J) analysis were used to analyze the deformation behavior. The best comprehensive mechanical properties were obtained by the introduction of the pearlite phase in B + PF dualphase with the tensile streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…Depending on the specific lamellae spacing and C content, widely varying trapping energies between 11 and 80 kJ mol are reported [42][43][44], resulting in a mixed classification as both shallow and deep traps. However, it is reported that introducing pearlite into a ferritic-bainitic dual-phase steel resulted in improved resistance to HE [45].…”
Section: Cavitiesmentioning
confidence: 99%
“…Depending on the specific lamellae spacing and C content, widely varying trapping energies between 11 and 80 kJ mol are reported [42][43][44], resulting in a mixed classification as both shallow and deep traps. However, it is reported that introducing pearlite into a ferritic-bainitic dual-phase steel resulted in improved resistance to HE [45].…”
Section: Cavitiesmentioning
confidence: 99%